Upaya Peningkatan Pengetahuan Mobilitas Fisik Post Stroke Pada Keluarga Tn.W Di Desa Sentul Mojolaban - WIBOWO, AGUS; , Agus Sudaryanto, S. Kep, Ns, M. Kes (2016)
Stroke is a major cause of disability in adults and penjadi number one cause of death in Indonesia. A large part of post-stroke patients will experience residual symptoms are highly variable, can be disturbances mobilization or movement disorders, vision problems, speech disorders, emotional changes, and other symptoms corresponding brain infarct location. Non hemoagik stroke events, especially in the working area of Puskesmas Mojolaban in February 2016 reached 7 cases. Associated with the data above, the writer interested to know about the family with stroke issues within the scope of family nursing. The author is motivated to make a report with the title Improving Physical Mobility Post Stroke In Tn Family. W In the village Mojolaban Sentul. Methods: In this report the authors use a case study method using the nursing process approach includes assessment, nursing diagnosis, planning, implementation, evaluation and documentation. Results: The whole family Ny. S understanding the disease state in the suffering Ny. S in the auxiliary treatment and care Ny. S teach family members to live independently and accept life as it is, can live. Families were able to recognize the health problems of disease and stroke in the face by Ny. S it is the show with the family aware of the impact of health problems resulting from stroke. Already widely nice family learned about the problems that occur in stroke. Families can take care of Ny. S if felt a recurrence of stroke in a doctor or the nearest hospital. Conclusion: Based on the results and the discussion it can be concluded that the nursing diagnoses that arise in the case of Ny. S with non-hemorrhagic stroke is generally physical mobility impairments related to the inability of families to know the health problems, especially non-hemorrhagic stroke that occurs in Ny. S. The intervention can be performed well, it is supported by the patient and family are cooperative, patient, willing to implement the recommended actions by nurses and practice well.